2021
DOI: 10.1002/ece3.8219
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological characterization of the freshwater mussel clubshell species complex (Pleurobema clava and Pleurobema oviforme) to inform conservation planning

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 160 publications
0
6
0
Order By: Relevance
“…For example, Johnson et al 4 used multiple lines of evidence to show that current taxonomy overestimated species diversity within the imperilled freshwater mussel genus Cyclonaias in North America. Similarly, Morrison et al 71 tested species boundaries in the North American Pleurobema species complex using genetic and morphological data, finding that the most likely scenario was that the two named species they investigated were members of a single, widespread species. Despite this growing trend of using multiple sources of evidence for species delimitation, several freshwater mussel taxa have been named based on shell morphology alone in recent decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Johnson et al 4 used multiple lines of evidence to show that current taxonomy overestimated species diversity within the imperilled freshwater mussel genus Cyclonaias in North America. Similarly, Morrison et al 71 tested species boundaries in the North American Pleurobema species complex using genetic and morphological data, finding that the most likely scenario was that the two named species they investigated were members of a single, widespread species. Despite this growing trend of using multiple sources of evidence for species delimitation, several freshwater mussel taxa have been named based on shell morphology alone in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…As more studies use an integrative approach for delineating freshwater mussel species, implications for conservation are inevitable, and this is likely to take place on a global scale. For example, the suggestion that the freshwater mussel species Pleurobema clava (listed as Endangered under the Endangered Species Act in the USA) and P. oviforme (a species being considered for listing) are members of a single, widespread species will have management implications for these species 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to investigate and recognize species limits in order to inform conservation actions. The so‐called pigtoe mussels (Tribe Pleurobemini; genera Fusconaia , Pleurobema , and Pleuronaia ), which are broadly distributed in river systems in central and eastern North America (Campbell & Lydeard, 2012b; Heard & Guckert, 1970), are such a group of freshwater mussels (Campbell & Lydeard, 2012a, 2012b; Inoue et al, 2018; Morrison et al, 2021; Schilling, 2015), and those of the Ohio River basin are yet to receive sufficient phylogenetic characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant example of closely related species is P. clava and P. oviforme , species endemic to the Tennessee and Cumberland River watersheds, for which Campbell et al (2008) showed few molecular differences at mtDNA genes between these taxa, although when assessed at nuclear ITS1 , differences were observed. More recently, Morrison et al (2021) conducted a rang‐wide assessment of mitochondrial (mtDNA) and nuclear microsatellite DNA and showed minimal mtDNA genetic divergence and even some haplotype sharing over wide geographic areas between the two taxa throughout the Ohio River basin, but very high divergence at microsatellite markers and distinctive morphology for a population occurring in the extreme headwaters of the upper Tennessee River basin. Therefore, utilization of nuclear as well as mitochondrial DNA sequences is critical for assessing phylogenetic differentiation among closely related species.…”
Section: Introductionmentioning
confidence: 99%
“…Unionids in the North American tribe Pleurobemini Hannibel, 1912 are prone to high levels of misidentification due to subtle interspecific differences and high levels of intraspecific variation in shell morphology (Campbell and Lydeard 2012;Inoue et al 2018). This has led to inaccurate taxonomic hypotheses for many species, and molecular data has shown to be useful in distinguishing species boundaries and their ranges in this group (Campbell and Lydeard 2012;Pieri et al 2018;Morrison et al 2021). The pleurobemine genus Fusco naia Simpson, 1900 consists of 13 species endemic to the United States and Canada (Williams et al 2017;Pieri et al 2018;Smith et al 2021).…”
Section: Introductionmentioning
confidence: 99%